Association of exposure to manganese and iron with striatal and thalamic GABA and other neurometabolites – neuroimaging results from the WELDOX II study - Casjens, Swaantje (Neurotoxicology, 2017)
OBJECTIVE: Magnetic resonance spectroscopy (MRS) is a non-invasive method to quantify neurometabolite concentrations in the brain. Within the framework of the WELDOX II study, we investigated the association of exposure to manganese (Mn) and iron (Fe) with γ-aminobutyric acid (GABA) and other neurometabolites in the striatum and thalamus of 154 men. MATERIAL AND METHODS: GABA-edited and short echo-time MRS at 3T was used to assess brain levels of GABA, glutamate, total creatine (tCr) and other neurometabolites. Volumes of interest (VOIs) were placed into the striatum and thalamus of both hemispheres of 47 active welders, 20 former welders, 36 men with Parkinson’s disease (PD), 12 men with hemochromatosis (HC), and 39 male controls. Linear mixed models were used to estimate the influence of Mn and Fe exposure on neurometabolites while simultaneously adjusting for cerebrospinal fluid (CSF) content, age and other factors. Exposure to Mn and Fe was assessed by study group, blood concentrations, relaxation rates R1 and R2* in the globus pallidus (GP), and airborne exposure (active welders only). RESULTS: The median shift exposure to respirable Mn and Fe in active welders was 23 μg/m(3) and 110 μg/m(3), respectively. Airborne exposure was not associated with any other neurometabolite concentration. Mn in blood and serum ferritin were highest in active and former welders. GABA concentrations were not associated with any measure of exposure to Mn or Fe. In comparison to controls, tCr in these VOIs was lower in welders and patients with PD or HC. Serum concentrations of ferritin and Fe were associated with N-acetylaspartate, but in opposed directions. Higher R1 values in the GP correlated with lower neurometabolite concentrations, in particular tCr (exp(β)=0.87, p<0.01) and choline (exp(β)=0.84, p=0.04). R2* was positively associated with glutamate-glutamine and negatively with myo-inositol. CONCLUSIONS: Our results do not provide evidence that striatal and thalamic GABA differ between Mn-exposed workers, PD or HC patients, and controls. This may be due to the low exposure levels of the Mn-exposed workers and the challenges to detect small changes in GABA. Whereas Mn in blood was not associated with any neurometabolite content in these VOIs, a higher metal accumulation in the GP assessed with R1 correlated with generally lower neurometabolite concentrations.